A New Measure of Foreign Rule Based on Genetic Distance - Dhammika Dharmapala (Center for Economic Studies and ifo Institute (CESifo), 2020)
The consequences for countries of past foreign rule are the subject of a vast literature across history and the social sciences. This paper constructs a novel measure of past foreign (or minority) rule - the genetic distance of a country's ruling elite in the year 1900 from the country's ethnic majority - by mapping historical information on these groups to existing data on bilateral genetic distances between countries and populations. This generates an "elite-population genetic distance" in 1900 (EPGD_1900) for each of 228 present-day countries and territories. While this continuous measure is positively correlated with existing dichotomous measures of foreign rule, it captures an additional dimension of variation absent from the existing measures. The paper documents robust conditional correlations between EPGD_1900 and current income levels, and between EPGD_1900 and current fiscal capacity (controlling for various relevant country characteristics, existing measures of foreign rule, the genetic distance of a country's ethnic majority from that of the UK, and continent fixed effects). In particular, both current GDP per capita and tax revenue as a percentage of GDP are substantially lower for countries and territories with higher EPGD_1900. While these relationships may be attributable to unobserved and persistent variation in state-building capabilities across societies, the results are robust to controlling for a widely-used index of state antiquity that measures the history of state-building capacity.
Keywords: O10; H20; 330; foreign rule; fiscal capacity; economic development